Effectiveness of oral appliances versus continuous positive airway pressure in treatment of OSA patients: An updated meta-analysis. Issue 6 (2nd November 2019) - Zhang, Menghan; Liu, Yuehua; Liu, Yuanshun; Yu, Fengyang; Yan, Shaowen; Chen, Lulu; Lv, Chenxing; Lu, Haiping
Abstract: Objective: To update the meta-analysis comparing the effectiveness of oral appliance (OA) with continuous positive airway pressure (CPAP) in treating patients with obstructive sleep apnea (OSA). Methods: PubMed, ISI Web of Knowledge, Ovid, EBSCO Dentistry & Oral Science Source, The Cochrane Library, and Embase database were searched for RCTs until 23 May 2017. Meta-analyses were performed using RevMan 5.3. Results: Sixteen RCTs were included. Compared with OA, CPAP significantly decreased AHI, min SaO2, ARI, ESS ( p  < 0.05), with no significant difference in REM%, FOSQ, BP ( p  ≥ 0.05). OA significantly improved REM% in the severe groups and ESS in the adjustable OA group ( p  < 0.05). OA shared greater preference. Conclusion: Even though CPAP can better decrease the severity of OSA, more patients opted for OA, which showed better results in severe patients, especially adjustable OA.